Die Duale Einkommensteuer des Sachverständigenrates in der Diskussion - Marc Oeffner (University of Würzburg, Department of Economics, 2005)
– This paper discusses the DIT, which is a tax reform proposal of the German Council of Economic Experts. Assessing an income tax system is a complex task. In doing so, you have to review the conditions of the international tax and locational competition, the ability-to-pay principle, the efficiency of the tax system, the possibilities of tax arbitrage and last but not least you have to balance this factors against the background of the costs of a reform concept. The conclusion of the paper is that the DIT is a too oversized and expensive concept to attract FDIs, which additionally creates diverse problems and hazards.
Keywords: 330